Oral Immunotherapy and Basophil and Mast Cell Reactivity in Food Allergy - Paranjape, Anuya; Tsai, Mindy; Mukai, Kaori; Hoh, Ramona A.; Joshi, Shilpa A.; Chinthrajah, R. Sharon; Nadeau, Kari C.; Boyd, Scott D.; Galli, Stephen J. (Frontiers in Immunology, 2020)
Basophil activation tests (BATs) can closely monitor, in vitro, a patient’s propensity to develop type I hypersensitivity reactions. Because of their high specificity and sensitivity, BATs have become promising diagnostic tools, especially in cases with equivocal clinical histories, skin prick test results, and/or levels of specific IgE to allergen extracts. BATs also are useful as tools for monitoring the effects of treatment, since oral immunotherapy (OIT) studies report a diminution in patients’ basophil responsiveness over the course of OIT. This review will discuss the BAT findings obtained before, during, and after OIT for food allergy. We will mainly focus on the association of basophil responsiveness, and alterations in basophil surface markers, with clinical outcomes and other clinical features, such as blood levels of specific IgG and IgE antibodies. The detailed analysis of these correlations will ultimately facilitate the use of BATs, along with other blood biomarkers, to differentiate short-term desensitization versus sustained unresponsiveness and to improve treatment protocols. Given the critical anatomic location of mast cells adjacent to the many IgE+ plasma cells found in the gastrointestinal tissues of allergic individuals, we will also discuss the role of gastrointestinal mast cells in manifestations of food allergies.